The borders, they are a-changin'! The emergence of socio-digital borders in the EU - Magdalena König (Internet Policy Review, 2016)
Relying on big data, modern surveillance becomes increasingly influential in determining societal power relations. Lyon argues that modern surveillance always categorises people entailing social effects, what he conceptualises as social sorting. This paper assesses if patterns of social sorting can be found in the EU surveillance systems for migration Schengen Information System (SIS), Visa Information System (VIS) and EUROpean DACtylographic comparison system (EURODAC), which are planned to be merged in order to ensure maximum efficiency in surveillance. To do so, the paper analyses relevant documents referring to SIS, VIS and EURODAC. These systems have assumed the traditional border function of deciding on societal inclusion and exclusion. I argue that, to some extent, socio-digital borders are drawn along the categories established through social sorting. The paper exemplifies how social sorting relying on big data may be a disempowering surveillance practice.
Keywords: 300; Social sorting; Borders; Big data